PENGEMBANGAN MEDIA POP UP BOOK PADA MATERI BANGUN RUANG DALAM EFEKTIVITAS PEMBELAJARAN KELAS V SEKOLAH DASAR - Mohammad Wildan Alifianto; Budiyono (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
The background of this research is the lack of concrete learning media used in the learning process. This study aims to produce valid, practical, and effective Pop-Up Book BaRung (Three-Dimensional Shapes) learning media for fifth-grade elementary school students. The research design uses the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). This study was conducted in grade V at SDN Lontar 481 Surabaya. The results showed a validity percentage of 82.5%, categorized as valid by media experts, and 90.76%, categorized as very valid by material experts. The practicality test yielded results of 88.77% from student questionnaires and 100% from teacher questionnaires, both categorized as very practical. The effectiveness of the media was demonstrated by a t-test showing a significant difference between pre-test and post-test scores, with an average N-Gain score of 0.624, categorized as moderate. This research produced Pop-Up Book BaRung (Three-Dimensional Shapes) learning media that is valid, practical, and effective. Keywords : Pop-Up Book BaRung Media, Effectiveness, Solid Geometry